Professional Education-Some Legal Aspects - Avhad, B. E. (Journal of Engineering Education Transformations, 1993)
Last year a Division Bench of the Supreme Court of India decided the case of Miss. Mohini Jain Vs. State of Karnataka and others and the decision had caused upheaval in the educational field . The Court held that Right, to Education is included in Right to Life.